Profiling of immune‐related gene expression in children with familial hypercholesterolaemia. (12th November 2019) - Narverud, I.; Christensen, J. J.; Bakke, S. S.; Ulven, S. M.; Rundblad, A.; Aukrust, P.; Espevik, T.; Bogsrud, M. P.; Retterstøl, K.; Ueland, T.; Halvorsen, B.; Holven, K. B.
Abstract: Background: Innate and adaptive immune responses are pivotal in atherosclerosis, but their association with early‐stage atherosclerosis in humans is incompletely understood. In this regard, untreated children with familial hypercholesterolaemia may serve as a human model to investigate the effect of elevated low‐density lipoprotein (LDL)‐cholesterol. Objectives: We aimed to study the immunological and inflammatory pathways involved in early atherosclerosis by examining mRNA molecules in peripheral blood mononuclear cells (PBMCs) from children with FH. Methods: We analysed the level of 587 immune‐related mRNA molecules using state‐of‐the‐art Nanostring technology in PBMCs from children with ( n = 30) and without ( n = 21) FH, and from FH children before and after statin therapy ( n = 10). Results: 176 genes (30%) were differentially expressed between the FH and healthy children at P < 0.05. Compared to healthy children, the dysregulated pathways in FH children included the following: T cells (18/19); B cells (5/6); tumour necrosis factor super family (TNFSF) (6/8); cell growth, proliferation and differentiation (5/7); interleukins (5/9); toll‐like receptors (2/5); apoptosis (3/7) and antigen presentation (1/7), where the ratio denotes higher expressed genes to total number of genes. Statin therapy reversed expression of thirteen of these mRNAs in FH children. Conclusion: FH children display higher PBMC expression of immune‐related genes mapped to several pathways, including T and B cells, and TNFSF than healthy children. Our results suggest that LDL‐C plays an important role in modulating expression of different immune‐related genes, and novel data on the involvement of these pathways in the early atherosclerosis may represent future therapeutic targets for prevention of atherosclerotic progression. Abstract :